Fisetin induces apoptosis through mitochondrial apoptosis pathway in human uveal melanoma cells. Issue 5 (31st January 2018) - Wang, Kai; Hu, Dan‐Ning; Lin, Hui‐Wen; Yang, Wei‐En; Hsieh, Yi‐Hsien; Chien, Hsiang‐Wen; Yang, Shun‐Fa
Abstract: Fisetin, a diatery flavonoid, been reported that possess anticancer effects in various cancers. The purpose of the study was to investigate the antitumor effects of fisetin in cultured uveal melanoma cell lines and compared with normal retinal pigment epithelial (RPE) cells. MTT assay was used for evaluating cytotoxic effects of fisetin. Flow cytometry study was used for the determination of apoptosis. JC‐1 fluorescent reader was used to determine mitochondrial transmembrane potential changes. The results shown that fisetin dose‐dependently decreased the cell viability of uveal melanoma cells but not influenced the cell viability of RPE cells. Apoptosis of uveal melanoma cells was induced by fisetin efficiently. Fisetin inhibited antiapoptotic Bcl‐2 family proteins and damaged the mitochondrial transmembrane potential. The levels of proapoptotic Bcl‐2 proteins, cytochrome c, and various caspase activities were increased by fisetin. In conclusion, fisetin induces apoptosis of uveal melanoma cells selectively and may be a promising agent to be explored for the treatment of uveal melanoma.